Major hazard industries disaster preparedness: an empirical study of liquefied petroleum gas storage facilities - Radin Umar, Radin Zaid; Ahmad, Nadiah; Mat Rashid, Rasyimawati (Inderscience Enterprises Ltd., 2023)
Liquefied petroleum gas (LPG) storage facilities storing more than 50 tonnes of LPG are classified as major hazard installations (MHIs). This industry involves highly flammable hydrocarbon chemicals that can cause destruction of property and endanger human lives. This study aims to investigate the level of disaster preparedness among 23 LPG storage facilities in Malaysia. The preparedness performance of the facilities was assessed through a five-point instrument measure in six preparedness domains. For overall preparedness, 60% of LPG facilities were rated poor or weak, and remaining 40% were rated as good or satisfactory. This indicates a serious gap in the overall current capacity of the majority of facilities to respond to major hazard disasters. Across all facilities, ‘risk assessment’ was the best performance domain, while the worst was ‘emergency exercise’. The findings provide an overview of the level of preparedness that can guide areas of improvement among LPG facilities in Malaysia.